ICG-mediated fluorescence-assisted debridement to promote wound healing. - Gang Zhu; Benjian Gao; Jun Fan; Jianfei Chen; Song Su; Xiaoli Yang; Bo Li; Cheng Fang (PLoS ONE, 2023)
The purpose of this study was to examine the efficacy of ICG-mediated fluorescence molecular imaging (FMI) in debridement of necrotic tissue. 96 wound-infected rats were randomly divided into control group, ICG group, excitation light (EL)group and FMI group for debridement of necrotic tissue (n = 24). (I) Control group: only debridement; (II) ICG group: ICG injection before debridement; (III) EL group: Debridement under EL; (IV) FMI group: Debridement guided by ICG-mediated FMI. On the 3rd, 6th, and 9th days, the wound tissues of the rats in each group were collected for histological examination, and the levels of serum interleukin-4 (IL-4) and interferon-γ (INF-γ) were analyzed. The wound healing rate, wound score and body weight of the rats in each group were followed up until the wound healed. The results showed that the infected wounds of the rats in the FMI group had significant fluorescence development. The level of serum IL-4 in the FMI group was higher than that in the other three groups on the 6th day (p<0.01), while the level of INF-γ was lower than that in the other three groups on the 6th and 9th day (p<0.05). The results of dynamic wound tissue H&E staining indicated that the wound healing in the FMI group was better than the other three groups. The in vivo follow-up results showed that the wound healing rate and wound score of the FMI group were better than the other three groups, and the growth of rats had no difference with the other groups. ICG-mediated FMI can achieve accurate imaging of necrotic tissue for debridement, and so can accelerate wound healing, which has good clinical application prospects.